PHYSICOCHEMICAL CHANGES DURING THE ROTATION PROCESS OF COMPLEX SULPHIDE ORE (Universal International Scientific Journal, 2026)
The article systematically analyzes the main physicochemical changes that occur during the roasting of complex gold-bearing sulfide ores. The studies shed light on the mechanisms of thermal processing, including the disruption of the crystal lattice of sulfide minerals, the release of sulfur in the form of SO₂ and other gaseous compounds, and the release of gold from the sulfide and aluminosilicate matrix. The thermodynamic conditions of the roasting process, phase changes occurring under the influence of temperature, the formation of intermediate oxide and sulfate compounds, and the composition and properties of the final products are discussed. The results obtained serve as a scientific and practical basis for increasing the efficiency of gold extraction and optimizing subsequent hydrometallurgical processes.
Keywords: gold-bearing sulfide ores; roasting process; physicochemical changes